2023
DOI: 10.1101/2023.03.07.531435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglial MHC-I induction with aging and Alzheimer’s is conserved in mouse models and humans

Abstract: Major Histocompatibility Complex I (MHC-I) function in the CNS is still being determined after previously being thought to be absent from the brain. MHC-I expression increases with brain aging in mouse, rat, and human whole tissue analyses. Neuronal MHC-I expression has been proposed to regulate developmental synapse elimination and tau pathology in Alzheimer's disease (AD). However, the CNS cellular localization of MHC-I expression has been unclear. Across newly generated and publicly available ribosomal prof… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 121 publications
1
4
0
Order By: Relevance
“…These data showed that resident immune cells upregulated MHC II and its pathway, suggesting their ability to present antigens to CD4 + helper T-cells. Supporting our results, similar interactions between MHC II + resident immune cells and CD4 + T-cells have been documented in other contexts, such as Tau-mediated neurodegeneration and aging in the murine brain (Askin & Wegmann, 2023; Kellogg et al, 2023; Zhang et al, 2022). In the retina, their interplay is well-characterized only in animal models of autoimmune uveitis (Lipski et al, 2017; Okunuki et al, 2019) and little is known in retinal degenerative diseases.…”
Section: Discussionsupporting
confidence: 90%
“…These data showed that resident immune cells upregulated MHC II and its pathway, suggesting their ability to present antigens to CD4 + helper T-cells. Supporting our results, similar interactions between MHC II + resident immune cells and CD4 + T-cells have been documented in other contexts, such as Tau-mediated neurodegeneration and aging in the murine brain (Askin & Wegmann, 2023; Kellogg et al, 2023; Zhang et al, 2022). In the retina, their interplay is well-characterized only in animal models of autoimmune uveitis (Lipski et al, 2017; Okunuki et al, 2019) and little is known in retinal degenerative diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that these differentially expressed genes (DEGs) are enriched in pathways such as Epstein-Barr virus infection, cell cycle and cellular senescence ( Figures 3 B and S3 D). Specifically, genes associated with aging and senescence such as H2-K1, H2-D1/Q6/Q4/Q7, H2-T22/23, GADD45a, and Igftbp3, 44 were upregulated in neurons treated with microglial apoE particles ( Figure 3 C). Meanwhile, genes associated with cellular mitosis and cell cycle 44 , 45 were downregulated after microglial apoE particles treatment, including Ccnb1, Ccna2, Ccnb2, Ccne2, Cdk1, and foxm1 45 , 46 ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, genes associated with aging and senescence such as H2-K1, H2-D1/Q6/Q4/Q7, H2-T22/23, GADD45a, and Igftbp3, 44 were upregulated in neurons treated with microglial apoE particles ( Figure 3 C). Meanwhile, genes associated with cellular mitosis and cell cycle 44 , 45 were downregulated after microglial apoE particles treatment, including Ccnb1, Ccna2, Ccnb2, Ccne2, Cdk1, and foxm1 45 , 46 ( Figure 3 C). Results from real-time (RT) PCR consistently validated differences in mRNA levels of these genes in neurons with different glial apoE particle treatments ( Figures 3 D and 3E).…”
Section: Resultsmentioning
confidence: 99%
“…We next wanted to further explore the relative expression of the proteins in resting and LPS‐sEVs that related to the cell surface as this may provide insight into defining the microglia phenotype sEVs are derived from (Figure 5B). Interestingly, among the 19 proteins there were notable proteins involved in inflammation such as complement component C3, and major histocompatibility complex (MHC) Class I molecules [33] were significantly enriched on the surface of LPS‐sEVs. Of the 8 significant GO biological process terms, fibrinolysis (GO:0042730) was the most significantly enriched term (Figure 5C) with an enrichment for plasminogen activator inhibitor‐1 (PAI‐1) and plasminogen (PLMN) (Figure 5D), proteins commonly upregulated in AD [34].…”
Section: Resultsmentioning
confidence: 99%